IMPLEMENTATION OF CAMBRIDGE INTERNATIONAL GENERAL CERTIFICATE OF SECONDARY EDUCATION CURRICULUM IN PLANT TRANSPORT SYSTEM TOPIC IN AN INTERNATIONAL SCHOOL - Keumala, Yuriza (2013)
The dynamics of schooling in Indonesia, started since the enactment of Law Number 20 Year 2003, indicate a paradigm shift in school management and the phenomenon of international schools in Indonesia has been growing as implied by this law. An International school is a school that promotes international education, in an international environment, either by adopting an international curriculum such as Cambridge International Curriculum. Due to that phenomena the research is conducted with the purpose to analyze the organization and implementation of Cambridge IGCSE Curriculum in of instructional process of Plant Transport System Topic by employing qualitative descriptive methodology. This research was done in one of international school in Bandung with one science teacher and one class of grade nine that consist of nine students, four females and five males as participants. The research data were collected through video, documents, interviews, and classroom observation. It is found that Cambridge IGCSE Biology syllabus provides what students need to develop and prepare for the next stage of their education and also help them develop their scientific skills, attitudes and their awareness of the nature of science and its relationship to the technology. While, in the implementation process there are data and information gap between objectives in Cambridge syllabus and implementation of syllabus in instructional process in the classroom. Keywords: Cambridge Curriculum, Curriculum Implementation, International School, Plant Transport System